Focus on the language learner : - Tarone, Elaine (Oxford University Press, 1999)
This book provides ideas, techniques, and procedures that will enable the practicing language teacher to better identify the local needs of particular groups of second language learners, and work toward meeting those needs. It includes numerous illustrative examples and practical exercises that can be adapted and use in the classroom